Top-down estimation of carbon monoxide emissions from the Mexico Megacity based on FTIR measurements from ground and space - W. Stremme; M. Grutter; C. Rivera; A. Bezanilla; A. R. Garcia; I. Ortega; M. George; C. Clerbaux; P.-F. Coheur; D. Hurtmans; J. W. Hannigan; M. T. Coffey (Atmospheric Chemistry and Physics, 2013)
Continuous carbon monoxide (CO) total column densities above the Universidad Nacional Autónoma de México (UNAM) campus in Mexico City have been derived from solar absorption infrared spectroscopic measurements since October 2007. Its diurnal evolution is used in the present study in conjunction with other ground-based and satellite data to develop a top-down emission estimate of the annual CO emission of the Mexico City Metropolitan Area (MCMA). The growth-rate of the total column around noon under low ventilation conditions is calculated and allows us to derive the average surface emission-flux at UNAM, while similar measurements taken at the edge of the MCMA in Tecámac provide information on background CO levels in the Mexico basin. Based on 3 yr of measurements, CO column measurements from the Infrared Atmospheric Sounding Interferometer (IASI) satellite instrument are used to reconstruct the spatial distribution of this anthropogenic pollutant over the MCMA. The agreement between the measured columns of the satellite and ground-based measurements is excellent, particularly when a comparison strategy based on time-displaced air masses is used. The annual emission of the Mexico Megacity is estimated to be (2.15 ± 0.5) Tg yr−1 for the year 2008, while the official inventory for that year reported 1.6 Tg yr−1. The difference is slightly higher than the conservative uncertainty estimated in this work suggesting that the emission might be underestimated by the conventional bottom-up method. A larger discrepancy is found in the spatial distribution of the emissions, when comparing the emission flux over UNAM (derived from the ground-based measurement) with that of the inventory integrated over a representative area. The methodology presented here represents a new and useful strategy to evaluate the contribution of megacities to the global anthropogenic gas emissions. Additionally, three different strategies to compare ground and space-based measurements above an inhomogeneous and strongly contaminated area like Mexico City are presented and discussed.